Method for preparing LATP solid electrolyte through molten salt driving

Through the method of molten salt driver preparation method, the LATP solid -state electrolyte powder preparation cost, complex process, and difficulty in mass production are solved in the existing technology, and the preparation of LATP solid electrolyte powder with high phase purity and high -ion conduction rate is suitable for preparation, which is suitable Large -scale mass production.

CN119381531APending Publication Date: 2025-01-28CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411582912.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, when preparing LATP solid electrolyte powder with high phase purity and high ionic conductivity, there are problems such as high raw material cost, complex process, difficult mass production, and high temperature roasting, resulting in volatility of lithium elements.

Method used

Adopting molten salt driver preparation methods, by mixing lithium, aluminum, titanium source, and low melting point phosphate according to chemical measurement, wet ball grind and dry, and then heat up at the melting point near the phosphate to promote the melting salt driving reaction. , Get a uniform and dense front -wheel drive, and obtain a high -phase purity LATP solid electrolyte powder through secondary roasting.

Benefits of technology

Latp solid electrolyte powder with low cost, simple process, high-phase purity, high-ion conductivity is suitable for large-scale mass production, and the ion conductivity at the normal temperature can reach 1.01 × 10-3S CM-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381531A_ABST
    Figure CN119381531A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid electrolyte preparation, and particularly discloses a method for preparing an LATP solid electrolyte through molten salt driving. The method comprises the following steps: respectively weighing a lithium source, an aluminum source, a titanium source and low-melting-point phosphate according to the stoichiometric ratio of the LATP solid electrolyte, mixing, carrying out wet ball milling, and drying to obtain raw material powder; performing long-time heat preservation on the raw material powder near the melting point of phosphate to obtain a precursor; and grinding the precursor, carrying out secondary roasting, and cooling to room temperature to obtain the catalyst. Liquid is formed after low-melting-point phosphate is molten, in the long-time heat preservation process, the phosphate liquid expands to wrap solid-phase particles such as a lithium source, an aluminum source and a titanium source, chemical reaction occurs, raw material powder slowly releases gas such as ammonia gas, carbon dioxide and water vapor, and the remaining raw material powder gradually shrinks to fill gaps under the wrapping and surface tension effect of a molten liquid phase; and a compact precursor with uniform composition is obtained, so that the ionic conductivity of the prepared LATP solid electrolyte is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to a method for preparing LATP solid electrolytes by molten salt driving. Background Art

[0002] Among many ceramic solid electrolytes, NASICON-type solid electrolyte LATP has attracted widespread attention due to its significant advantages and broad development prospects due to its advantages such as high room temperature lithium ion conductivity, good air stability and low synthesis cost.

[0003] Common LATP preparation methods include solid phase reaction method, sol-gel method, coprecipitation method and hydrothermal method. Among them, the powder phase purity obtained by liquid phase preparation methods such as sol-gel method and hydrothermal method is high, but there are problems such as expensive and toxic raw material cost, high requirements for production environment, and great difficulty in mass production. In the solid phase reaction method, the reaction raw materials are usually some solid oxides, which have the advantages of low raw material cost, simple process, and low requirements for production environment. It is suitable for large-scale mass production and has broad market prospects. However, the solid phase reaction method has poor raw material mixing uniformity, and high temperature roasting is usually required to promote element diffusion to obtain solid electrolyte, but high temperature roasting is easy to cause volatilization of lithium element, so the LATP solid electrolyte prepared by the solid phase reaction method usually has impurities such as TiO2 and AlPO4, so that the ionic conductivity is low.

[0004] Patent CN202110690168.X discloses a method for preparing a new type of LGSP solid electrolyte, which adopts solid-phase synthesis. In the precursor preparation, the materials are mixed and ground evenly, with diammonium phosphate as the phosphorus source and lithium carbonate as the lithium source, and dried at 200°C for 20 hours, and then heated to 450°C at 5°C / min and maintained for 2 hours to release volatile components.

[0005] The academic paper "Molten Salt Driven Conversion Reaction Enabling Lithiophilicand Air-Stable Garnet Surface for Solid-State Lithium Batteries" reveals that a conversion reaction driven by molten NH4H2PO4 salt is used to establish Li3PO4 on the surface of garnet-type solid electrolyte to replace Li2CO3 pollutants. The highly fluid NH4H2PO4 molten salt helps the formation of Li3PO4 and achieves air-stable garnet-type solid electrolyte by preventing the reaction of H2O / CO2 in the air.

[0006] Currently, there are few reports on using phosphate melt-driven reactions to improve the ionic conductivity of LATP solid electrolytes. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing LATP solid electrolyte driven by molten salt in view of the deficiencies in the prior art, and to prepare LATP solid electrolyte powder with high phase purity and high ionic conductivity on a large scale by a simple, economical and efficient preparation method.

[0008] To achieve the above object, the present invention adopts the following technical solution: The present invention provides a method for preparing LATP solid electrolyte by molten salt driving, comprising the following steps: S1. According to the stoichiometric ratio of the LATP solid electrolyte, a lithium source, an aluminum source, a titanium source and a low melting point phosphate are weighed and mixed, and then wet-milled and dried to obtain a raw material powder; the low melting point phosphate is ammonium dihydrogen phosphate or diammonium hydrogen phosphate; S2, keeping the raw material powder at a temperature near the melting point of phosphate for a long time, and driving the reaction by melting the phosphate to obtain a precursor; S3, grinding the precursor, calcining it twice, and cooling it to room temperature to obtain LATP solid electrolyte powder.

[0009] Furthermore, in step S1, the lithium source is any one of lithium carbonate, lithium hydroxide or lithium acetate.

[0010] Furthermore, in step S1, the aluminum source is one or a combination of Al2O3 and Al(OH)3.

[0011] Furthermore, in step S1, the titanium source is any one of rutile phase, anatase phase or amorphous titanium dioxide.

[0012] Furthermore, the amount of the lithium source added is 2% to 10% more than the stoichiometric ratio.

[0013] Furthermore, in step S1, the wet ball milling process is as follows: the ball milling jar is made of corundum, the ball milling beads are small zirconia balls, the ball milling medium is isopropanol, the ball milling speed is 300-500 rpm, and the ball milling time is 2-5 hours.

[0014] Furthermore, in step S1, the drying temperature is 70-120° C., and the drying time is 2-10 hours.

[0015] Furthermore, in step S2, the preset temperature is 180-190°C, and the insulation time is 5-10 days.

[0016] Furthermore, in step S3, the secondary calcination process is carried out at 2-10°C min -1 The heating rate is first raised to 500~750℃ and kept for 4~8h, then continued at 2~10℃ min -1The temperature is raised to 850~950℃ at a heating rate and kept at this temperature for 5~15h.

[0017] The second object of the present invention is to provide a LATP solid electrolyte prepared by the above-mentioned method for preparing LATP solid electrolyte driven by molten salt.

[0018] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: (1) The molten salt-driven method for preparing LATP solid electrolyte provided by the present invention, wherein the low melting point phosphate refers to one or a combination of phosphorus sources NH4H2PO4 and (NH4)2HPO4, (NH4)2HPO4, and NH4H2PO4 is decomposed at 155°C to obtain NH4H2PO4, and NH4H2PO4 is a low melting point substance, which begins to melt and transform into a liquid at about 180°C to 190°C, accompanied by slow decomposition. The raw material powder of the present invention is kept at 180 to 190°C for 5 to 10 days to undergo a molten salt-driven reaction to obtain a precursor with uniform composition and compactness. The low melting point compound NH4H2PO4 is kept at 180 to 190°C to melt and form a liquid. During the long-term heat preservation process, the phosphate liquid expands and wraps the solid phase particles of the lithium source, aluminum source, titanium source, etc. and undergoes a chemical reaction, thereby promoting the homogenization of the raw material powder composition. In addition, during the molten salt driven reaction, the raw material powder will slowly release gases such as ammonia, carbon dioxide, and water vapor, and the remaining raw material powder will gradually shrink and fill the gaps under the encapsulation of the molten liquid phase and the action of surface tension, making the raw material powder densified. Therefore, in the present invention, by adding phosphorus sources NH4H2PO4 and (NH4)2HPO4, and keeping the temperature for a long time within the melting point temperature range of NH4H2PO4, the raw material composition is promoted to be homogenized and densified.

[0019] (2) The uniform and dense precursor is calcined to obtain LATP solid electrolyte powder with high phase purity and high ionic conductivity. The ionic conductivity can reach 1.01×10 -3 S cm -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the sample morphology of the raw material powder of Example 1 kept at 180°C for 1 day; Figure 2 XRD diagram of LATP solid electrolyte powder prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 3 The full spectrum refinement of the XRD pattern of the LATP solid electrolyte powder prepared in Example 1; Figure 4 This is a SEM image of the LATP solid electrolyte powder prepared in Example 1; Figure 5This is a SEM image of the LATP solid electrolyte powder prepared in Example 1 pressed into a solid electrolyte sheet; Figure 6a This is an EIS graph of the LATP solid electrolyte powder prepared in Example 1 pressed into a solid electrolyte sheet; Figure 6b This is an EIS graph of the LATP solid electrolyte powder prepared in Example 2 pressed into a solid electrolyte sheet; Figure 6c This is an EIS graph of the LATP solid electrolyte powder prepared in Example 3 pressed into a solid electrolyte sheet; Figure 6d This is an EIS graph of the LATP solid electrolyte powder prepared in Example 4 pressed into a solid electrolyte sheet; Figure 6e This is an EIS graph of the LATP solid electrolyte powder prepared in Comparative Example 1 pressed into a solid electrolyte sheet; Figure 6f This is an EIS graph of the LATP solid electrolyte powder prepared in Comparative Example 2 pressed into a solid electrolyte sheet; Figure 6g This is a graph showing the ionic conductivity test results of Example 1. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0022] The present invention provides a method for preparing LATP solid electrolyte by molten salt driving, comprising the following steps: S1. According to the stoichiometric ratio of the LATP solid electrolyte, a lithium source, an aluminum source, a titanium source and a low melting point phosphate are weighed and mixed, and then wet-milled and dried to obtain a raw material powder; S2, keeping the raw material powder at a temperature near the melting point of the phosphate for a long time, and driving the reaction of the low melting point phosphate by melting to obtain a precursor with uniform composition and compactness; the low melting point phosphate is ammonium dihydrogen phosphate or diammonium hydrogen phosphate; S3, grinding the precursor, calcining it twice, and cooling it to room temperature to obtain LATP solid electrolyte powder.

[0023] This method is suitable for the preparation of LATP solid electrolyte, which can be Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3, etc.

[0024] In some embodiments, in step S1, the wet ball milling process is as follows: the ball milling jar is made of corundum, the ball milling beads are small zirconia balls, the ball milling medium is isopropanol, the ball milling speed is 300-500 rpm, the ball milling time is 2-5 hours, the drying temperature is 70-120° C., and the drying time is 2-10 hours.

[0025] It should be noted that although it is desired that the precursors are present in a ratio to provide the above-mentioned general product, the lithium compound may be present in an excess of about 2% to 10% lithium compared to the stoichiometric precursor body mixture. The lithium compound may be lithium carbonate, lithium hydroxide, and lithium acetate. Since lithium carbonate has a very high melting point and generally reacts with other precursors before melting, it is preferably used for solid-state reactions. Lithium carbonate has a melting point above 600°C and it decomposes in the presence of other precursors and / or reacts with other precursors before melting. In contrast, lithium hydroxide melts at about 400°C. Certain reaction temperatures of 500°C to 750°C are preferred herein, preferably at 2 to 10°C min -1 The heating rate is first raised to 500-750℃ and kept at this temperature for 4-8 hours. Lithium hydroxide will melt before any significant reaction with other precursors occurs to an effective extent. This melting reaction is difficult to control. At the same time, to ensure that the obtained LATP solid electrolyte powder also has high ionic conductivity, a secondary calcination at 850-950℃ is selected, preferably at 2-10℃ min -1 The temperature is raised to 850~950℃ at a heating rate and kept at this temperature for 5~15 h.

[0026] Usually, the raw materials of the above-mentioned precursors can be crystals, particles, powders, and are usually in granular form. The molten phosphate preferably uses ammonium dihydrogen phosphate or diammonium hydrogen phosphate. Ammonium dihydrogen phosphate can be melted at 180-190°C to form a liquid phase, and the preferred insulation time is 5-10 days. The phosphate liquid phase gradually expands and wraps the solid particles of lithium source, aluminum source, titanium source, etc., directly reacts chemically with the solid particles, and drives the raw material powder to shrink and densify for a long time, ensuring sufficient time for the precursor components to be uniform and densified.

[0027] The aluminum source can be selected from one of Al2O3, Al(OH)3 or a combination of the two, and the titanium source can be selected from any one of rutile phase, anatase phase or amorphous titanium dioxide.

[0028] The following is a detailed description of a method for preparing LATP solid electrolyte driven by molten salt provided by the present invention with reference to specific embodiments.

[0029] Example 1 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0030] The specific steps are as follows: (1) Weigh 1.3839 g Li2CO3, 3.7261 g TiO2, 0.4197 g Al2O3, and 9.4702 g NH4H2PO4, place them in a corundum ball mill, mix and mill them, and dry them in a 75°C drying oven to obtain raw material powder; (2) The raw material powder is kept at 180°C for 10 days to obtain a precursor; (3) The precursor was heated at 3℃ min -1 The temperature was raised to 700 °C at a heating rate of 3 °C min -1 The temperature was raised to 900°C at a heating rate and kept at this temperature for 6 h to obtain LATP electrolyte powder.

[0031] Example 2 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0032] The method is basically the same as Example 1, except that the raw material powder is kept at 180° C. for 5 days to obtain the precursor.

[0033] Example 3 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0034] The method is basically the same as Example 1, except that the raw material powder is kept at 180° C. for 3 days to obtain the precursor.

[0035] Example 4 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0036] The method is basically the same as Example 1, except that the raw material powder is kept at 180° C. for 1 day to obtain the precursor.

[0037] Example 5 This embodiment provides a Li1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0038] The method is basically the same as Example 1, except that the raw material powder is kept at 185° C. for 10 days to obtain the precursor; Example 6 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0039] The same as Example 1, except that the raw material powder is kept at 190° C. for 7 days to obtain the precursor; Example 7 This embodiment provides a Li 1.4 Al 0.4 Ti 1.6 Preparation method of (PO4)3 electrolyte.

[0040] Basically the same as Example 1, except that according to Li 1.4 Al 0.4 Ti 1.6 The stoichiometric ratio of (PO4)3 is Li2CO3, TiO2, Al2O3, and NH4H2PO4.

[0041] Example 8 This embodiment provides a Li 1.5 Al 0.5 Ti 1.5 Preparation method of (PO4)3 electrolyte.

[0042] Basically the same as Example 1, except that according to Li 1.5 Al 0.5 Ti 1.5 Weigh Li2CO3, TiO2, Al2O3, and NH4H2PO4 in the stoichiometric ratio of (PO4)3.

[0043] Comparative Example 1 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0044] The specific steps are as follows: (1) Weigh 1.3839 g Li2CO3, 3.7261 g TiO2, 0.4197 g Al2O3, and 9.4702 g NH4H2PO4, place them in a corundum ball mill, mix and mill them, and dry them in a 75°C drying oven to obtain raw material powder; (2) Raw powder at 3℃ min -1 The temperature was raised to 700 °C at a heating rate of 3 °C min -1 The temperature was raised to 900°C at a heating rate and kept at this temperature for 6 h to obtain LATP electrolyte powder.

[0045] Comparative Example 2 This embodiment provides a Li 1.3 Al 0.3 Ti 1.7 Preparation method of (PO4)3 electrolyte.

[0046] The specific steps are as follows: (1) Weigh 1.3839 g Li2CO3, 3.7261 g TiO2, 0.4197 g Al2O3, and 9.4702 g NH4H2PO4, place them in a corundum ball mill, mix and mill them, and dry them in a 75°C drying oven to obtain raw material powder; (2) Raw powder at 3℃ min -1 The temperature was raised to 400 °C at a rate of 3 °C min -1 The temperature was raised to 700 °C at a heating rate of 3 °C min -1 The temperature was raised to 900°C at a heating rate and kept at this temperature for 6 h to obtain LATP electrolyte powder.

[0047] refer to Figure 1 , which is the sample morphology of the raw material powder of Example 1 after being kept at 180°C for the first day. It can be seen from the figure that the raw material powder obviously liquefies and shrinks, proving that the raw material powder partially melts and decomposes during the process, promoting the uniformity and densification of the raw material composition. The present invention finds that when the holding time is observed for up to 10 days, the melting state of the raw material powder is very similar, and it is observed to be increasingly densified, and a precursor with uniform composition and density is obtained.

[0048] refer to Figure 2 , which is the XRD diagram of the LATP solid electrolyte powder prepared in Example 1, Comparative Example 1 and Comparative Example 2. It can be seen that Li 1.3 Al 0.3 Ti 1.7 (PO4)3 electrolyte powder.

[0049] refer to Figure 3 , which is a full spectrum refinement of the XRD pattern of the LATP solid electrolyte powder prepared in Example 1, indicating that the present invention can obtain LATP solid electrolyte powder with high phase purity.

[0050] refer to Figure 4, is a SEM image of the LATP solid electrolyte powder prepared in Example 1, showing that the particle size of the LATP solid electrolyte powder is larger.

[0051] Ionic conductivity test: The ionic conductivity test was performed on the electrolyte sheets prepared using the LATP solid electrolyte powder prepared in Examples 1-8 and Comparative Examples 1-2.

[0052] Preparation of LATP electrolyte sheet: Weigh 1 g of LATP electrolyte powder and place it in an agate mortar, add 5 drops of PVA binder drop by drop, and grind for 30 min to obtain a mixed powder. Weigh 0.25 g of the mixed powder and press it into a tablet with a tablet pressure of 5 MPa and a holding time of 5 min to obtain a LATP electrolyte sheet. The obtained LATP electrolyte sheet was calcined at 1°C min -1 Heating rate: 500℃, 4 h, 3℃ min -1 The temperature was raised to 900°C at a heating rate of , kept at that temperature for 6 h, and cooled to room temperature to obtain LATP electrolyte sheets.

[0053] The LATP solid electrolyte powders obtained in Examples 1 to 8 were pressed into solid electrolyte sheets and all had similar SEMs. Figure 5 As shown, it is a SEM image of the LATP solid electrolyte powder obtained in Example 1 pressed into a solid electrolyte sheet, showing that the particle size is large and the distribution is concentrated, and the interface contact between the particles is more uniform. The LATP solid electrolyte obtained by the method of the present invention has a significantly improved ion conductivity compared with the common method of preparing LATP by solid phase reaction.

[0054] The effect of molten salt holding time on ionic conductivity was investigated. Figure 6a-6f As shown, the EIS graphs of the LATP solid electrolyte powders prepared in Examples 1-4, Comparative Example 1 and Comparative Example 2 are shown. Figure 6g The ionic conductivity of the LATP solid electrolyte prepared by heat preservation for 1d, 3d, 5d, and 10d is shown in Table 1. When the heat preservation time is 5-10d, the ionic conductivity of the LATP solid electrolyte prepared by molten salt driving is 0.534×10 -3 ~1.010×10 -3 S cm -1 .

[0055] Table 1. Ionic conductivity test results.

[0056]

[0057] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing LATP solid electrolyte driven by molten salt, characterized in that: The following steps are involved: S1. According to the stoichiometric ratio of the LATP solid electrolyte, a lithium source, an aluminum source, a titanium source and a low melting point phosphate are weighed and mixed, and then wet-milled and dried to obtain a raw material powder; the low melting point phosphate is ammonium dihydrogen phosphate or diammonium hydrogen phosphate; S2, keeping the raw material powder at a temperature near the melting point of the phosphate for a long time, and the low melting point phosphate melts to drive the reaction to obtain a precursor with uniform composition and compactness; S3, grinding the precursor, calcining it twice, and cooling it to room temperature to obtain LATP solid electrolyte powder.

2. The method according to claim 1, characterized in that In step S1, the lithium source is any one of lithium carbonate, lithium hydroxide or lithium acetate.

3. The method according to claim 1, characterized in that In step S1, the aluminum source is one or a combination of Al2O3 and Al(OH)3.

4. The method according to claim 1, characterized in that In step S1, the titanium source is any one of rutile phase, anatase phase or amorphous titanium dioxide.

5. The method according to claim 2, characterized in that The amount of the lithium source added is 2% to 10% more than the stoichiometric ratio.

6. The method according to claim 1, characterized in that In step S1, the wet ball milling process is as follows: the ball milling jar is made of corundum, the ball milling beads are small zirconia balls, the ball milling medium is isopropanol, the ball milling speed is 300-500 rpm, and the ball milling time is 2-5 hours.

7. The method according to claim 1, characterized in that In step S1, the drying temperature is 70-120° C., and the drying time is 2-10 hours.

8. The method according to claim 1, characterized in that In step S2, the preset temperature is 180-190°C and the insulation time is 5-10 days.

9. The method according to claim 1, wherein In step S3, the secondary calcination process is carried out at 2-10°C min -1 The heating rate is first raised to 500~750℃ and kept for 4~8h, then continued at 2~10℃ min -1 The temperature is raised to 850~950℃ at a heating rate and kept at this temperature for 5~15h.

10. A LATP solid electrolyte prepared by the method for preparing a LATP solid electrolyte driven by molten salt as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Novel LGSP solid electrolyte and preparation method thereof

    CN113422108A